Evaluation of Structural Properties and Catalytic Activities in Knoevenagel Condensation Reaction of Zeolitic Imidazolate Framework-8 Synthesized under Different Conditions - Pham Dinh Du; Nguyen Viet Duy Thanh; Nguyen Trung Hieu (Advances in Materials Science and Engineering)
In the present study, the zeolitic imidazolate framework-8 (ZIF-8) was synthesized at both room temperature and high temperatures. The effects of solvents, molar ratios of precursors, reaction time, and temperature on the structural properties of the as-prepared materials were investigated. Moreover, the surface morphologies of the obtained specimens were characterized using X-ray diffraction, scanning electron microscopy, Fourier-transform infrared spectroscopy, and nitrogen adsorption methods. The results show that ZIF-8 was formed in methanol and water at room temperature and in dimethylformamide (DMF) at high temperatures. Further, in methanol, the molar ratios of precursors and reaction time have negligible effects on the morphologies and structures of ZIF-8; however, in DMF, the reaction temperature has a significant influence on the microstructures of ZIF-8. The catalytic activities of the obtained materials were evaluated using the Knoevenagel condensation reaction, and ZIF-8 proves to be an excellent solid base catalyst.